Galectin-3 secreted by triple-negative breast cancer cells regulates T cell function - Annat Raiter; Yael Barhum; Julia Lipovetsky; Chen Menachem; Sharona Elgavish; Shmuel Ruppo; Yehudit Birger; Shai Izraeli; Orna Steinberg-Shemer; Rinat Yerushalmi (Neoplasia: An International Journal for Oncology Research)
Triple-negative breast cancer (TNBC) is an aggressive subtype that accounts for 10-15 % of breast cancer. Current treatment of high-risk early-stage TNBC includes neoadjuvant chemo-immune therapy. However, the substantial variation in immune response prompts an urgent need for new immune-targeting agents. This requires a comprehensive understanding of TNBC's tumor microenvironment. We recently demonstrated that Galectin-3 (Gal-3) binding protein/Gal-3 complex secreted by TNBC cells induces immunosuppression, through inhibiting CD45 signaling in T cells. Here, we further investigated the interaction between secreted Gal-3 and T cells in TNBC.Using CRISPR/Cas9 gene editing of the TNBC MDA-MB-231 cell-line, we obtained Gal-3 negative(neg) clones. We studied these in an in-vitro model, co-cultured with peripheral blood mononuclear cells (PBMC) to imitate immune-tumor interaction, and in an in-vivo model, when implanted in mice.Gal-3neg tumors in mice had decelerated tumor growth after PBMC inoculation. In contrast, the Gal-3 positive(pos) tumors continued growing despite PBMC inoculation, and tumor T regulatory cell (CD4/FoxP3+) infiltration increased. RNA sequencing of T cells from women with TNBC with elevated plasma levels of Gal-3 revealed significantly lower expression of oxidative phosphorylation genes than in T cells from healthy women. Similarly, in our in-vitro model, the decreased expression of oxidative phosphorylation genes and mitochondrial dysfunction resulted in a significant increase in CD8 intracellular reactive oxygen species. Consequently, T exhausted cells (CD8/PD1/Tim3/Lag3+) significantly increased in PBMC co-cultured with Gal-3pos TNBCs.To conclude, we revealed a novel TNBC-related Gal-3 suppressor mechanism that involved upregulation of CD4 T regulatory and of CD8 T exhausted cells.